Efficacy and Safety of Apatinib for the Treatment of Advanced or Recurrent Cervical Cancer: A Single-Arm Meta-Analysis Among Chinese Patients - Huang, Da; He, Qionghua; Zhai, Lingyun; Shen, Jiayu; Jing, Fei; Chen, Huanhuan; Zhu, Xiaoqing; Zhou, Jianwei (Frontiers in Pharmacology, 2022)
Background: Although various effective compounds for the second- and third-line treatment of recurrent or metastatic cervical cancer improved the overall survival, the optimal regimen remains controversial. Previous studies revealed that apatinib had extensive antitumor activity. However, almost all studies on apatinib in recurrent cervical cancer are non-randomized controlled trials with small sample sizes, different first-line treatments and uncontrolled statistical analysis, which may result in a lack of accurate measurement for evaluating the efficacy and safety of apatinib. Here, this meta-analysis aims to evaluate efficacy and safety of apatinib in patients with recurrent or metastatic cervical cancer. Methods: Relevant studies retrieved from the PubMed, EMBASE, the Cochrane Library and Web of Science databases. Outcomes including overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS) and adverse events (AEs) were extracted to analyze. Results: Eight studies involving 278 patients were enrolled in this meta-analysis. In terms of tumor response, the pooled ORR and DCR were 27.5% and 70.9%, respectively. With regard to survival analysis, the pooled PFS and OS were 5.19 months and 10.63 months, respectively. The most common treatment-related adverse events of apatinib were hand-foot syndrome (all grade: 39.6%, ≥grade III: 7.5%), hypertension (all grade: 42.0%, ≥grade III: 13.1%), and fatigue (all grade: 32.0%, ≥grade III: 8.0%). Conclusions: In summary, the findings in this meta-analysis demonstrated that apatinib was proven efficacy and safety for patients with recurrent cervical cancer.